Implementasi Digital pada Tata Kelola Administrasi: Upaya Meningkatkan Mutu Pelayanan di Era Birokrasi Modern - Pratiwi, Saskia Firina; Zalukhu, Lano Alvin; Tesa, Aulia Rahma; Aisyah, Iqra’ Syahadatul; J, Jumiati; Saputra, Boni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This literature review discusses digital implementation in administrative governance as a strategy to improve the quality of public services in the era of modern bureaucracy. Technological developments encourage transformation in the delivery of public services, requiring the bureaucracy to be more efficient, transparent, and responsive to community needs. Through the implementation of the Electronic-Based Government System (SPBE) and the digitization of public services, administrative processes that were previously slow and complicated can now be simplified, service times are faster, and accountability and community participation are stronger. The study results show that the implementation of digital platforms such as service applications, websites, and social media not only improves public satisfaction, but can also ease access to information and administrative procedures. However, the digitization process still faces challenges, especially in infrastructure gaps, digital literacy, and unprepared human resources, especially in remote areas such as Papua. The literature emphasizes that digitization can be a strategy for change towards data-driven, collaborative, and service-oriented governance. With a strategic and inclusive approach, digital transformation can be the foundation for the realization of an adaptive and equitable modern bureaucracy.